Die Radionuklidventrikulo- graphie - eine nichtinvasive Methode zur Diagnose und Quantifizierung der Trikuspidalklappeninsuffizienz - Kress, P.; Waitzinger, J.; Seibold, H.; Wieshammer, S.; Richter, P.; Bitter, F.; Adam, W. E.; Stauch, M. (Nuklearmedizin - NuclearMedicine, 1987)
The diagnosis of tricuspid regurgitation (TR) is difficult to make by simple clinical methods or by invasive techniques. Contrast echocardiography and Doppler echocardiography have improved diagnostic results, but a golden standard is still not available. Radionuclide ventriculography (RNV) is a well- established method for the detection and quantification of a volume load on the left ventricle: the regurgitation fraction can simply be derived from the regurgitant index as the ratio of enddiastolicendsystolic count-rate differences between the left and right ventricle. In left heart valvular regurgitation a regurgitant index exceeding the upper normal limit can be expected. This study was performed to evaluate the diagnostic accuracy of an abnormally low regurgitant index in detecting TR, which is accompanied by an isolated volume load on the right ventricle. A series of 33 patients with TR on physical examination and cardiac catheterization underwent RNV and was compared with 48 patients with right ventricular enlargement or pressure load on the right ventricle. In addition, the specificity of the method was evaluated in 470 consecutive patients with various forms of heart disease. In 18 out of 20 subjects with isolated TR a regurgitant index below the lower normal limit was found. The remaining 2 cases with minor TR had a regurgitant index within the normal range, which is 0.89 to 1.97 in this laboratory. In patients with additional volume load on the left ventricle, the sensitivity of the method was found to be low, as could be expected from the principle of the method. The time-activity curve over the liver was usually in phase with that recorded over the atria in subjects with TR. Therefore, the additional examination of a region of interest over the liver was particularly useful in these patients with concomitant aortic or mitral valve regurgitation. None of the 48 patients with right ventricular enlargement or pressure load on the right ventricle had a falsely positive result. A total of 17 out of 470 consecutive patients had a regurgitant index below the normal range; left ventricular function was severely impaired in 9 of these patients. The remaining subjects had a regurgitant index slightly below the lower normal limit. In conclusion, RNV has a high sensitivity in the diagnosis of TR in patients without left heart valvular regurgitation and a high specificity in patients without severely impaired left ventricular function and without left-to-right shunt through an atrial septal defect. As in patients with right ventricular volume load from an atrial septal defect, RNV appears to allow the quantification of TR. This, however, cannot be proven directly since a golden standard for quantification of TR is not available.